Face à l'histoire 1933 1996 : L'artiste moderne devant l'événement historique. - Ameline, J. P. (Paris : Flammarion, 1996)
Abramovic, Marina ; Aillaud, Gilles ; Alvermann, Hans Peter ; Angeli, Franco ; Appel, Karel ; Arroyo, Eduardo ; Art & Language ; Atkinson, Conrad ; Baj, Enrico ; Bazaine, Jean ; Beckmann, Max ; Bellmer, Hans ; Beuys, Joseph ; Blumenfeld, Erwin ; Boetti, Alighiero ; Boulatov, Erik ; Brauner, Victor ; Broodthaers, Marcel ; Brunius, Jacques ; Buren, Daniel ; Burgin, Victor ; Butler, Reg ; Camnitzer, Luis ; Caniaris, Vlassis ; Chagall, Marc ; Consagra, Pietro ; Constant ; Cremer, Fritz ; Cueco, Henri ; Dali, Salvador ; Davis, Stuart ; Deïneka, Alexandre ; Delarbre, Léon ; Depero, Fortunato ; Dewasne, Jean ; Dittborn, Eugenio ; Dix, Otto ; Doherty, Willie ; Donagh, Rita ; Dorazio, Piero ; Duchamp, Marcel ; Dufrêne, François ; Duhamel, Jacques ; Elso, Juan Francisco ; Equipo Cronica ; Equipo Realidad ; Ernst, Max ; Errò ; Fabro, Luciano ; Fahlström, Öyvind ; Farocki, Harun ; Fautrier, Jean ; Fleischmann, Karel ; Fougeron, André ; Freundlich, Otto ; Fritta, Bedrich ; Fromanger, Gérard ; Gabo, Naum ; Gerz, Jachen ; Gilioli, Emile ; González, Julio ; Grosz, George ; Gruber, Francis ; Grundig, Lea ; Guston, Philip ; Gutov, Dmitri ; Guttuso, Renato ; Haacke, Hans ; Hains, Raymond ; Hamilton, Richard ; Hasior, Wladyslaw ; Heartfield, John ; Heerup, Henry ; Heldt, Werner ; Herbin, Auguste ; Herold, Georg ; Himid, Lubaina ; Hofer, Karl ; Horsfield, Craigie ; Huang Yong Ping ; Hudecek, Frantisek ; Immendorff, Jörg ; Indiana, Robert ; IRWIN ; Ito, Kosho ; Jacobsen, Egill ; Jones, Kim ; Jorn, Asger ; Kabakov, Ilya ; Kaprow, Allan ; Kelly, Mary ; Klee, Paul ; Kokoschka, Oskar ; Kolar, Jiri ; Koller, Julius ; Kollwitz, Kathe ; Komar & Melamid ; Kulik, Oleg ; Kuprianov, Vladimir ; Lawrence, Jacob ; Lefrancq, Marcel G. ; Leger, Fernand ; Levine, Jack ; etc
boek